Changes in household wealth in communities living in proximity to a large-scale copper mine in Zambia. (December 2021) - Zabré, Hyacinthe R.; Farnham, Andrea; Diagbouga, Serge P.; Fink, Günther; Divall, Mark J.; Winkler, Mirko S.; Knoblauch, Astrid M.
Abstract: Large-scale mining can alter the living conditions of surrounding communities in positive and negative ways. A health impact assessment conducted in the context of a newly developed large-scale copper mine in rural Zambia gave us the opportunity to measure changes in health determinants over time. We conducted periodic household surveys at baseline in 2011, during the construction phase in 2015 and during the operational phase in 2019. Data collected included economic indicators that were based on the standardized list of household assets used in the Zambia Demographic and Health Survey, which we subsequently converted into a wealth score using principal component analysis. We compared mean wealth scores in six communities directly impacted by the mine with comparison communities, as well as the rest of the North-Western province of Zambia. A difference-in-differences linear regression model was used to compare changes over time. Mean wealth of the communities near the mine was significantly lower at baseline than that of the North-Western province (−0.54 points; p-value<0.001) in 2011, but surpassed the regional average in 2019 (+1.07 points; p-value <0.001). Mean wealth increased more rapidly in communities directly impacted by mine than in the comparison communities (+0.30 points, p-value <0.001). These results suggest a positive impact on living conditions in communities living near this copper mine. Our findings underscore the potential of the mining sector to contribute to economic development in Zambia. Highlights: Household wealth in a large-scale copper mining area showis positive economic impacts on the communities. Mean household wealth near the mine was lower at baseline than that of the surrounding province, but surpassed it by 2019. Mean household wealth increased more rapidly in communities directly impacted by mine than in nearby comparison communities. The mining sector has the potential to contribute to economic development in Zambia if impacts are appropriately managed.